2019
DOI: 10.3389/fmicb.2019.02027
|View full text |Cite
|
Sign up to set email alerts
|

Myrtenol Attenuates MRSA Biofilm and Virulence by Suppressing sarA Expression Dynamism

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a deleterious human pathogen responsible for severe morbidity and mortality worldwide. The pathogen has attained high priority in the World Health Organization (WHO) – Multidrug-resistant (MDR) pathogens list. Emerging MDR strains of S. aureus are clinically challenging due to failure in conventional antibiotic therapy. Biofilm formation is one of the underlying mechanisms behind the antibiotic resistance. Hence, attenuating biofilm formation has become an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 73 publications
6
68
0
Order By: Relevance
“…Similar results of myrtenol antibiofilm activity were found by Selvaraj et al [ 14 ], whose data show that myrtenol attenuates MRSA biofilm considerably, in addition to inhibiting the production of major virulence factors of MRSA, such as lipase, hemolysin and staphyloxanthin. In addition, it affected the slime synthesis, autoaggregation, autolysis, and eDNA production in MRSA.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results of myrtenol antibiofilm activity were found by Selvaraj et al [ 14 ], whose data show that myrtenol attenuates MRSA biofilm considerably, in addition to inhibiting the production of major virulence factors of MRSA, such as lipase, hemolysin and staphyloxanthin. In addition, it affected the slime synthesis, autoaggregation, autolysis, and eDNA production in MRSA.…”
Section: Resultssupporting
confidence: 87%
“…As part of the context of natural products, myrtenol is a phytoconstituent present in Myrtus communis L. (Myrtaceae) essential oil [ 9 ], which ethnopharmacological studies revealed to be used in folk medicine for several purposes, including antimicrobial [ 10 ]. Although anxiolytic [ 11 ], anti-inflammatory [ 12 ] and gastroprotective [ 13 ] activity of isolated myrtenol has been reported; its antibacterial and antibiofilm potential is still poorly described [ 14 ]. Given these facts, this study aimed to investigate the myrtenol activity against S. aureus , also analyzing its effect in combination with conventional antibacterial drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, antibiofilm agents are reported to potentiate the efficacy of antibiotics against bacterial biofilm when combined with antibiotics. Plenty of compounds with antibiofilm activity have been identified from various natural resources so far ( Abraham et al, 2012 ; Sethupathy et al, 2016 , 2017 ; Selvaraj et al, 2019 ; Valliammai et al, 2019 ). Thymol is a major constituent in the essential oil of thyme plant ( Thymus vulgaris ), and it is known to have various biological properties such as antibacterial, antifungal, antioxidant, and cognitive-enhancing activities ( Braga, 2005 ; Tohidpour et al, 2010 ; Azizi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several environmental factors such as glucose, salt (NaCl), ethanol, high temperature, antibiotics stress, and low oxygen have been described to support biofilm formation in S. aureus ( Jefferson, 2004 ; Fitzpatrick et al, 2005 ). Recent studies have focused on the development of antimicrobial drugs to inhibit the formation of biofilm and/or other virulence factors which appear promising with regards to controlling bacterial infections without spreading resistance ( Lee et al, 2013 , 2014 , 2016 ; Phuong et al, 2017 ; Kong et al, 2018 ; Selvaraj et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%